Calcitonin gene-related peptide receptor antagonist BIBN4096BS regulates synaptic transmission in the vestibular nucleus and improves vestibular function via PKC/ERK/CREB pathway in an experimental chronic migraine rat model - Tian, Ruimin; Zhang, Yun; Pan, Qi; Wang, Yunfeng; Wen, Qianwen; Fan, Xiaoping; Qin, Guangcheng; Zhang, Dunke; Chen, Lixue; Zhang, Yixin; Zhou, Jiying (Journal of headache and pain, 2022)
Background Vestibular symptoms are frequently reported in patients with chronic migraine (CM). However, whether vestibular symptoms arise through overlapping neurobiology of migraine remains to be elucidated. The neuropeptide calcitonin gene-related peptide (CGRP) and CGRP1 receptor play important pathological roles in facilitating central sensitization in CM. Therefore, we aimed to investigate whether CGRP1 receptor contributes to vestibular dysfunction after CM by improving synaptic transmission in the vestibular nucleus (VN). Methods A CM rat model was established by recurrent intermittent administration of nitroglycerin (NTG). Migraine- and vestibular-related behaviors were assessed. CGRP1 receptor specific antagonist, BIBN4096BS, and protein kinase C (PKC) inhibitor chelerythrine chloride (CHE) were administered intracerebroventricularly. The expressions of CGRP and CGRP1 receptor components, calcitonin receptor-like receptor (CLR) and receptor activity modifying protein 1 (RAMP1) were evaluated by western blot, immunofluorescent staining and quantitative real-time polymerase chain reaction in the vestibular nucleus (VN). Synaptic associated proteins and synaptic morphological characteristics were explored by western blot, transmission electron microscope, and Golgi-cox staining. The expressions of PKC, phosphorylated extracellular signal regulated kinase (p-ERK), phosphorylated cAMP response element-binding protein at serine 133 site (p-CREB-S133) and c-Fos were detected using western blot or immunofluorescent staining. Results The expressions of CGRP, CLR and RAMP1 were significantly upregulated in CM rats. CLR and RAMP1 were expressed mainly in neurons. BIBN4096BS treatment and PKC inhibition alleviated mechanical allodynia, thermal hyperalgesia and vestibular dysfunction in CM rats. Additionally, BIBN4096BS treatment and PKC inhibition markedly inhibited the overexpression of synaptic associated proteins and restored the abnormal synaptic structure in VN after CM. Furthermore, BIBN4096BS treatment dysregulated the expression levels of PKC, p-ERK and p-CREB-S133, and attenuated neuronal activation in VN after CM. Conclusions The present study demonstrated that CGRP1 receptor inhibition improved vestibular function after CM by reversing the aberrant synaptic transmission via downregulating PKC/ERK/CREB signaling pathway. Therapeutic interventions by inhibiting CGRP/CGRP1 signaling may be a new target for the treatment of vestibular symptoms in CM.